2005
DOI: 10.1107/s0907444904027118
|View full text |Cite
|
Sign up to set email alerts
|

Structure of aBacillus halmapalusfamily 13 α-amylase, BHA, in complex with an acarbose-derived nonasaccharide at 2.1 Å resolution

Abstract: PDB Reference: BHA±nonasaccharide complex, 1w9x, r1w9xsf.The enzymatic digestion of starch by -amylases is one of the key biotechnological reactions of recent times. In the search for industrial biocatalysts, the family GH13 -amylase BHA from Bacillus halmapalus has been cloned and expressed. The three-dimensional structure at 2.1 A Ê resolution has been determined in complex with the (pseudo)tetrasaccharide inhibitor acarbose. Acarbose is found bound as a nonasaccharide transglycosylation product spanning the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…Boel et al, 1990;Nielsen et al, 2003), was not observed for AmyD. In the 3D structure of bacterial GH13_5 family enzymes, a triad of metal ions (Ca 2+ -Na + -Ca 2+ ) has been observed between domain A and domain B, and an additional Ca 2+ ion has been located between domain A and domain C (Davies et al, 2005;Machius et al, 1998;Brzozowski et al, 2000). The amino acids interacting with these Ca 2+ ions are only partly conserved among the fungal GH13_5 family enzymes; the presence of bound Ca 2+ ions in these enzymes therefore appears less likely.…”
Section: Discussionmentioning
confidence: 99%
“…Boel et al, 1990;Nielsen et al, 2003), was not observed for AmyD. In the 3D structure of bacterial GH13_5 family enzymes, a triad of metal ions (Ca 2+ -Na + -Ca 2+ ) has been observed between domain A and domain B, and an additional Ca 2+ ion has been located between domain A and domain C (Davies et al, 2005;Machius et al, 1998;Brzozowski et al, 2000). The amino acids interacting with these Ca 2+ ions are only partly conserved among the fungal GH13_5 family enzymes; the presence of bound Ca 2+ ions in these enzymes therefore appears less likely.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, superimposition of barley, B. amyloliquefaciens, B. licheniformis, and B. halmapalus a-amylases, and Bacillus sp. 707 maltohexaose-producing amylase showed a shared S-shaped P 9 subsite cleft [3,5,27,28] with an internal barrier manifested by lack of enzyme-sugar hydrogen bonds at subsite À3. Remarkably, at subsite À6 Trp140 in maltohexaose-producing amylase, a conserved tryptophan in Bacillus a-amylases, and Tyr105 in AMY1 superimpose perfectly with rmsd of back bone atoms <0.1 Å (not shown).…”
Section: Comparison With Other A-amylasesmentioning
confidence: 99%
“…Structural studies of ␣-amylases in complex with substrate analogues have received much attention in the past decade (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The pseudotetrasaccharide inhibitor acarbose was used for the vast majority of these studies.…”
mentioning
confidence: 99%